A pilot study of loss aversion for drug and non-drug commodities in cocaine users. (1st November 2017) - Strickland, Justin C.; Beckmann, Joshua S.; Rush, Craig R.; Stoops, William W.
Highlights: Loss aversion was tested in active cocaine users. Cocaine users showed equal sensitivity to losses and gains. Performance was similar under uncertain (risky) and certain conditions. Performance was similar for drug (cocaine) and non-drug commodities. Abstract: Background: Numerous studies in behavioral economics have demonstrated that individuals are more sensitive to the prospect of a loss than a gain (i.e., loss aversion). Although loss aversion has been well described in "healthy" populations, little research exists in individuals with substance use disorders. This gap is notable considering the prominent role that choice and decision-making play in drug use. The purpose of this pilot study was to evaluate loss aversion in active cocaine users. Methods: Current cocaine users (N = 38; 42% female) participated in this within-subjects laboratory pilot study. Subjects completed a battery of tasks designed to assess loss aversion for drug and non-drug commodities under varying risk conditions. Standardized loss aversion coefficients (λ) were compared to theoretically and empirically relevant normative values (i.e., λ = 2). Results: Compared to normative loss aversion coefficient values, a precise and consistent decrease in loss aversion was observed in cocaine users (sample λ ≈ 1). These values were observed across drug and non-drug commodities as well as under certain and risky conditions. Conclusions: These data represent the first systematic study of loss aversion in cocaine-using populations and provide evidence for equal sensitivity to losses and gains or loss equivalence. Futures studies should evaluate the specificity of these effects to a history of cocaine use as well as the impact of manipulations of loss aversion on drug use to determine how this phenomenon may contribute to intervention development efforts.